Characteristics of successful grass-root sport club's governance: a case study Jyväskylän Naisvoimistelijat - Suomalainen, Janita (2017)
Grass-root sport clubs have a substantial role of delivering services for people of all ages, as well as a deep-rooted traditions and history in national competitive sports in Finland. Hence, voluntary boards that govern the clubs have a pivotal role of ensuring the quality of delivering the clubs’ services to consumers, through governance. Therefore, the aim of this qualitative case study is to depict what good governance practices can be found from a successful Finnish grass-root sport club’s board’s practices and operations that make the whole organization successful, as well as to provide suggestions for the particular board how to improve its towards higher quality governance.